Innovation Project Portfolio Management - Soontrakom, Vorapol (My University, 2012)
Companies today are forced to innovate in order to remain within business. Such innovation projects undertaken by the companies are defined in this study as creative ideas which have been managed through “Stage-Gate” innovation process. This process is used to manage innovation projects as they proceed from being newly created to ready for launching/implementing. This has ensured that the companies manage the innovation project right. However, with so many new creative ideas the companies can come up within limited resources, the companies must rely on Innovation Project Portfolio Management (IPPM) to ensure that they are managing only the right innovation projects. Although, there are many tools and techniques available for use within Project Portfolio Management, there is still no consensus on which are the most effective and no standard framework has been established especially for IPPM. Thus, this study proposes a practical framework for which individual innovative organization can follow as a guideline to manage its innovation project portfolio. The study theoretically first addresses the key differences between project portfolio management of innovation projects and other traditional projects - one of which is the stage nature of innovation projects due to their unclear objectives from the beginning compare to clearly established objectives of traditional projects. Secondly, different tools and techniques which can be used are examined based on the three goals of IPPM: (1) Maximizing the Value of Innovation Project Portfolio: Financial Methods, Decision Trees, Scoring Models and Checklists; (2) Balancing Innovation Project Portfolio: Visual Representations; and (3) Aligning Innovation Project Portfolio with Strategy: Bottom-Up (Scoring Models with Strategic Criteria) and Top-Down (Strategic Buckets). Finally, the two approaches in which IPPM can be integrated with Stage-Gate innovation process are discussed: (1) Gates- Dominated; and (2) Portfolio Reviews-Dominated. Practically, this study investigates IPPM of a case organization, and through analysis of the case study results proposes a practical framework for case organization to improve its current management of innovation project portfolio. This framework is then generalized to propose a final practical framework or guideline for which an innovative organization can follow to manage its innovation project portfolio.